2020
DOI: 10.3390/metabo10110434
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Metabolome Coverage and Evaluation of Matrix Effects by the Use of Experimental-Condition-Matched 13C-Labeled Biological Samples in Isotope-Assisted LC-HRMS Metabolomics

Abstract: Stable isotope-assisted approaches can improve untargeted liquid chromatography-high resolution mass spectrometry (LC-HRMS) metabolomics studies. Here, we demonstrate at the example of chemically stressed wheat that metabolome-wide internal standardization by globally 13C-labeled metabolite extract (GLMe-IS) of experimental-condition-matched biological samples can help to improve the detection of treatment-relevant metabolites and can aid in the post-acquisition assessment of putative matrix effects in samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Native plants were cultivated in the glass house without 13 CO 2 and harvested at the flowering stage as described by Ceranic and colleagues [38]. Briefly summarized, the plants were removed from the pot and remaining soil was washed from the roots with water.…”
Section: Fresh Root Samplesmentioning
confidence: 99%
“…Native plants were cultivated in the glass house without 13 CO 2 and harvested at the flowering stage as described by Ceranic and colleagues [38]. Briefly summarized, the plants were removed from the pot and remaining soil was washed from the roots with water.…”
Section: Fresh Root Samplesmentioning
confidence: 99%
“…Currently, the analytical challenges in metabolomics include the need to integrate data derived from more than one platform to produce more robust data and a wider metabolome coverage, maximizing the detection of possible metabolites in the target system (see Aliferis and Jabaji, 2011;Ćeranić et al, 2020;Roca et al, 2021 for reviews). Recent studies are showing that this integration is particularly powerful.…”
Section: Advanced Cross-platform Data Integrationmentioning
confidence: 99%
“…For the matrix effect assessment and correction, the postextraction spiking method is more suitable for targeted metabolomics due to the requirement of authentic standards. Hence, PCI is recommended as a more appropriate tool for matrix effect evaluation in untargeted metabolomics, , but only few studies about its application have been reported. , Although stable isotope labeling has also been applied to matrix effect evaluation in untargeted metabolomics, this technique is limited to specific sample types like yeast, cells, or plants due to the requirement of a globally labeled growth medium. …”
Section: Introductionmentioning
confidence: 99%